2020
DOI: 10.1200/jco.19.02983
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Genomic Analysis in NRG Oncology/RTOG 9802: A Phase III Trial of Radiation Versus Radiation Plus Procarbazine, Lomustine (CCNU), and Vincristine in High-Risk Low-Grade Glioma

Abstract: PURPOSE NRG Oncology/RTOG 9802 (ClinicalTrials.gov Identifier: NCT00003375 ) is a practice-changing study for patients with WHO low-grade glioma (LGG, grade II), as it was the first to demonstrate a survival benefit of adjuvant chemoradiotherapy over radiotherapy. This post hoc study sought to determine the prognostic and predictive impact of the WHO-defined molecular subgroups and corresponding molecular alterations within NRG Oncology/RTOG 9802. METHODS IDH1/2 mutations were determined by immunohistochemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
112
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(119 citation statements)
references
References 26 publications
6
112
1
Order By: Relevance
“…The RTOG 9802 trial reported a major prolongation of OS with the addition of PCV polychemotherapy to radiotherapy (54 Gy), from 7.8 years to 13.3 years in patients with high-risk WHO grade 2 gliomas who were 18–39 years of age and had undergone a subtotal resection or biopsy or in those aged ≥40 years 75 . This benefit was reported across histological subgroups and, although cohort sizes were small, benefit was observed in patients with either IDH-mutant astrocytomas or oligodendrogliomas but not in those with IDH-wild-type tumours 87 . Thus, radiotherapy followed by PCV constitutes the standard of care for patients with WHO grade 2 IDH-mutant astrocytomas deemed to require post-surgical treatment.…”
Section: Therapy — Specific Recommendationsmentioning
confidence: 85%
“…The RTOG 9802 trial reported a major prolongation of OS with the addition of PCV polychemotherapy to radiotherapy (54 Gy), from 7.8 years to 13.3 years in patients with high-risk WHO grade 2 gliomas who were 18–39 years of age and had undergone a subtotal resection or biopsy or in those aged ≥40 years 75 . This benefit was reported across histological subgroups and, although cohort sizes were small, benefit was observed in patients with either IDH-mutant astrocytomas or oligodendrogliomas but not in those with IDH-wild-type tumours 87 . Thus, radiotherapy followed by PCV constitutes the standard of care for patients with WHO grade 2 IDH-mutant astrocytomas deemed to require post-surgical treatment.…”
Section: Therapy — Specific Recommendationsmentioning
confidence: 85%
“…Importantly, the large majority of IDH-mt gliomas present with MGMT methylation, resulting in limited additional predictive potential in IDH-mt gliomas [25]. This was also confirmed by a recently published post-hoc analysis on the RTOG 9802 trial, which is further discussed below [26]. However, in a subsequent analysis of the single-arm RTOG 0424 phase II trial investigating the addition of TMZ to radiotherapy only, MGMT was shown as an IDH-independent prognostic marker in high-risk WHO grade II glioma [27].…”
Section: Tablementioning
confidence: 53%
“…The benefit of adjuvant PCV was most pronounced in IDH-mt grade II gliomas for both OS (HR 0.43, p = 0.009) and PFS (HR = 0.36, p < 0.001). Recently, the results of a post-hoc analysis incorporating further genetic markers have been published [26]. Most importantly, the beneficial effect of adjuvant PCV remained significant in both IDH-mt/1p19q-codeleted oligodendroglioma and IDH-mt astrocytoma in terms of OS and PFS, whereas the addition of PCV had no effect in the IDH-wt subgroup.…”
Section: Who Grade II Glioma (Idh-mt)mentioning
confidence: 99%
“…This negative result may be attributed to the heterogeneity of LGG, especially across the different molecular subgroups. As a most important biomarker, IDH mutation status deeply influences the pathophysiology of LGG, from survival to therapy response [ 2 , 15 ]. Tumors with IDH mutations, especially those accompanied by 1p/19q codeletion, may be sensitive to radiotherapy.…”
Section: Discussionmentioning
confidence: 99%